The effects of sexuality on depression and self-harm amongst adolescents - Gabriela Sigurðardóttir 1990- (2016)
The purpose of this research was to examine the relationship between sexual orientation, depression and self-harm. Parental support was also examined to see if it affected the relationship. Data was collected by the Icelandic Centre for Social Research and Analysis (ICSRA) by population-wide cross-sectional data from the 2013 Youth in Iceland study. The participants in the study were Icelandic high school students who attended school the day the questionnaire was submitted. Participants were 11.116 in total and a random sample of 2048 participants. There were two hypotheses tested. The first hypothesis was that individuals who are part of a minority group show higher levels of depression and self-harm. The second hypothesis was that teenage girls show higher levels of depressive symptoms and self-harm than boys. The results of the study indicated that participants who were part of a sexual minority group reported higher levels of depression and self-harm and the group that reported the highest levels of depression and self-harm were bisexual girls. Keywords: Sexuality, depression, parental support, sexual minority, self-harm. Tilgangur rannsóknarinnar var að rannsaka sambandið milli kynhneigðar, þunglyndis og sjálfsskaða. Stuðningur frá foreldrum var einnig kannaður til að sjá hvort hann hefði áhrif á sambandið. Gögn voru fengin frá Rannsóknum og greiningu úr þýðisrannsókn þeirra “Ungt fólk” frá árinu 2013. Þátttakendur rannsóknarinnar voru íslenskir framhaldsskólanemar sem mættu í skólann þegar rannsóknin var lögð fyrir. Þátttakendur voru alls 11.116 og notað var tilviljunarkennt úrtak sem samanstóð af 2048 þátttakendum. Tvær tilgátur voru prófaðar í þessari rannsókn. Fyrsta tilgátan var sú að einstaklingar sem voru í minnihlutahóp sýndi meiri þunglyndiseinkenni og sjálfsskaða. Seinni tilgátan var sú að unglings stúlkur sýndi meiri þunglyndiseinkenni og sjálfsskaða en strákar. Niðurstöður rannsóknarinnar gáfu til kynna að þátttakendur sem voru í minnihlutahóp þegar kom að kynhneigð sýndi meiri ...